2018
DOI: 10.1093/sleep/zsy044
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disruption as a predictor of quality of life among patients in the subpopulations and intermediate outcome measures in COPD study (SPIROMICS)

Abstract: ClinicalTrials.gov NCT01969344.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
(30 reference statements)
2
25
0
Order By: Relevance
“…Poor sleep quality in COPD has previously been associated with reduced health-related quality of life 7,9 and reduced physical activity during the day. 17 However, to our knowledge, this study is the first population-based longitudinal analysis evaluating exacerbation risk in Data are presented as median (interquartile range) or No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor sleep quality in COPD has previously been associated with reduced health-related quality of life 7,9 and reduced physical activity during the day. 17 However, to our knowledge, this study is the first population-based longitudinal analysis evaluating exacerbation risk in Data are presented as median (interquartile range) or No.…”
Section: Discussionmentioning
confidence: 99%
“…8 Sleep quality is an important predictor of health-related quality of life in COPD. [7][8][9] Acute exacerbations of COPD are common in the course of the disease and lead to deterioration in health status and increased mortality. 10 Therefore, there has been a growing interest in sleep quality in COPD and its effect on exacerbations.…”
mentioning
confidence: 99%
“…Previous studies have reported sleep problems in patients with COPD using COPD‐specific and non‐COPD‐specific measures. The majority of sleep studies in COPD have relied on two non‐disease‐specific measures, that is, the Pittsburgh Sleep Quality Index and/or the Epworth Sleep Scale . These generic measures, which cover broadly defined domains such as functional status and perceptions, may not perform well in patients with COPD considering no data of reliability or validity tests to justify their use in this population .…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality is impaired in patients with chronic respiratory disease [3] and diminished sleep efficiency with a reduction in REM sleep has been reported in patients with COPD, which correlates with awake arterial oxygen tension (P aO 2 ) but not with the degree of airflow obstruction [4], although lung hyperinflation has been associated with poor sleep quality in COPD patients [5]. Sleep disturbance in COPD is associated with reduced quality of life measures such as the Short Form-12 and the St George's Respiratory Questionnaire [6].…”
Section: Introductionmentioning
confidence: 99%